ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENYERAPAN TENAGA KERJA PADA INDUSTRI MAKANAN DAN MINUMAN DI KOTA SURABAYA - UMNIATI, NADIAH; ARIF, SJAMSUL (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
ABSTRACTThis study aims to analyze the factors that affect the absorption of labor in the food and beverage industry in the city of Surabaya either simultaneously (simultaneously) or partially (calculated each variable).Â Factors analyzed include wage rates, economic growth and number of business units. The type of data in this study is quantitative data and data sources used are secondary data obtained from the Central Bureau of Statistics Surabaya. This research uses multiple linear regression analysis model. In the calculation using multiple linear regression analysis model of the results of this study is if all the variables simultaneously significant effect.Â On the other hand, partially only the variable of wage level is not significant but the variable of economic growth and the number of business unit is significant. The results showed that there are two significant variables, namely economic growth and number of business units and there is one variable that is not significant ie wage rate variable. Then it can be concluded that the higher economic growth and the number of business units will increase the amount of labor absorbed. The higher the wage rate, the less the number of workers who survive.Keywords: Employment Absorption, Wage Level, Economic Growth, Number of Business Units.